2011
DOI: 10.4296/cwrj3602849
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Air Temperature on Water Temperature and the Concentration of Dissolved Oxygen in Newfoundland Rivers

Abstract: Abstract:In this paper regression models are developed for predicting water temperature and the concentration of dissolved oxygen in rivers monitored by the Newfoundland and Labrador Real-Time Water Quality Monitoring (RTWQM) network. The developed models can be used to predict mean, maximum and minimum water temperatures and dissolved oxygen at the monthly, weekly and daily time scales. A nonlinear logistic model is found to best represent the S-shaped relationship between water temperature at the real-time s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 28 publications
3
50
0
1
Order By: Relevance
“…Although seasonal differences in macroinvertebrate-community abundance and composition have long been reported in literature [48][49][50][51][52], community-shifts in their habitat preferences have not been studied; we assume that such 'shifting behavior' may be associated with the seasonal fluctuation of environmental variables, which are known primary drivers of BMI-community changes, that is, shading, water temperature and dissolved oxygen [53]. As summer approaches, shading from the surrounding riparian vegetation is reduced, the water temperature increases, the dissolved oxygen concentration decreases [54] and consequently, faster flowing, deeper, better oxygenated habitats provide shelter against the changing environment. In contrast to the under-studied seasonal shifts, typological differences in the habitat preferences of BMIs have been previously documented, suggesting a preference for shallower water depths and lower velocities in smaller rivers [15,55].…”
Section: Seasonal and Temporal Variation In The Habitat Preferences Omentioning
confidence: 99%
“…Although seasonal differences in macroinvertebrate-community abundance and composition have long been reported in literature [48][49][50][51][52], community-shifts in their habitat preferences have not been studied; we assume that such 'shifting behavior' may be associated with the seasonal fluctuation of environmental variables, which are known primary drivers of BMI-community changes, that is, shading, water temperature and dissolved oxygen [53]. As summer approaches, shading from the surrounding riparian vegetation is reduced, the water temperature increases, the dissolved oxygen concentration decreases [54] and consequently, faster flowing, deeper, better oxygenated habitats provide shelter against the changing environment. In contrast to the under-studied seasonal shifts, typological differences in the habitat preferences of BMIs have been previously documented, suggesting a preference for shallower water depths and lower velocities in smaller rivers [15,55].…”
Section: Seasonal and Temporal Variation In The Habitat Preferences Omentioning
confidence: 99%
“…The objective was to determine the impact of climatic variables (precipitation and air temperature) on the water temperature to DO concentration relationship. Because studies have revealed the relationship between DO and water temperature to be strongly negative [46], in an effort to identify the best regression model that suited water temperature and DO concentration in the tropical climate, it was determined that the exponential model was found to be better suited to modeling low DO concentrations at higher water temperatures in temperate climate [46]. In addition, the relationship between the changes in streamflow to water temperature and DO concentration were presented using the regression model.…”
Section: Evaluation Of Scenariosmentioning
confidence: 99%
“…Studies have shown that as time scale increases (daily, weekly, monthly), the regression of water and air temperature improved significantly [6,9,13,29]. Therefore, logistic regression models between daily mean water and air temperatures were also developed for the eight rivers in AL.…”
Section: Calculated Hourly Water Temperature From Daily Temperature Rmentioning
confidence: 99%
“…Studies have shown that as the time scale increases (daily, weekly, monthly, and annually), the model will be more accurate and reliable in estimating water temperatures [6,8,9,13,24]. The logistic regression model has been recently and widely used to estimate river water temperature [3,[25][26][27][28][29]. Morrill et al [28] evaluated the general temperature relationships (both linear and nonlinear) in 43 river and stream sites in 13 countries and indicated that the air/water temperature relationship is better fitted with non-linear regression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation